Immunodepression by Rowson-Parr Virus in Mice. I. Growth Curves of Rowson-Parr Virus and Immunological Relationships with Friend Virus - Bendinelli, M. (1973)
The growth curve of Rowson-Parr virus (RPV) was studied in the spleen of mice infected with RPV only and of mice infected with Friend virus (FV) preparations, which consist of a mixture of RPV and FV. In mice infected with FV preparations, RPV replicated to a higher titer than FV and attained higher levels than in singly infected mice. The chronic viremia of RPV-infected mice was found to coexist with circulating anti-RPV antibodies. These antibodies also neutralize FV and are probably responsible for the resistance against FV conferred to mice by prior infection with RPV.